Performance of five Mexican safflower (Carthamus tinctorius L.) varieties/breeding lines under Indian conditions: PERFORMANCE OF MEXICAN SAFFLOWER VARIETIES/BREEDING LINES UNDER INDIAN CONDITIONS - P PADMAVATHI; P RATNAKUMAR; P KADIRVEL; N MUKTA; P YADAV (Journal of Oilseeds Research, 2019)
Safflower (Carthamus tinctoriusL.), a drought tolerant crop, is capable of extractingmoisture fromdeeper layers ofsoil. In India, more than 80 per cent of safflower is cultivated in Vertisols of Peninsular region during post-rainy season under residual soil moisture conditions. Five Mexican varieties/breeding lines (Ciano-Lin, CCC-B4, RC-1033-L, CCC-B2 and CW-99) were evaluated in 2014-15 under irrigated conditions along with two Indian varieties (NARI-57 and PBNS-12). Significant variation was found between Mexican varieties/breeding lines and Indian varieties with respect to plant height, days to first flowering, number of capitula/plant, seed yield, biological yield, oil content and oil yield. Seed and oil yield of CCC-B2 (2259; 800 kg/ha) was on par with that of NARI-57 (2298; 719 kg/ha). The Ciano-Lin recorded significantly low seed (1266 kg/ha) and oil yield (399 kg/ha).